'I saw what the future direction would be…': Experiences of diabetes risk and physical activity after diabetes screening. (10th February 2014) - Vähäsarja, Kati; Kasila, Kirsti; Kettunen, Tarja; Rintala, Pauli; Salmela, Sanna; Poskiparta, Marita
<x xml:space="preserve">Abstract</x> Objectives To improve understanding of how individuals at high risk of type 2 diabetes experience the risk of diabetes and how these experiences relate to the adoption of physical activity as a protective behaviour. Design A qualitative study using semi‐structured interview with individuals identified by screening as at high risk of type 2 diabetes. Methods Fourteen individuals, aged 40–64, were interviewed twice, with a 2‐year interval between. Participants' experiences of their risk of diabetes and physical activity were assessed. The transcribed interview data were analysed using inductive qualitative content analysis. Results Two themes emerged from the data: a threatening risk perception and a rejected risk perception. The threatening risk perception occurred when the risk was unexpected by the participant, but became internalized through the screening procedure. The threatening perception also involved a commitment to increase physical activity to prevent diabetes. However, short‐term anxiety and subsequently emerging hopelessness were also part of this perception. The rejected risk perception involved indifference and scepticism regarding the risk. Here, physical activity behaviour and cognitions appeared to remain unchanged. Rejection also involved difficulties in accepting one's high‐risk identity. The rejecting group lacked motivation for increased physical activity, while the other group showed determination regarding increased physical activity, often leading to success. Conclusion Perceptions of the risk of diabetes emerged as threatening or as rejected. Participants' perceptions reflected varying and intertwining emotional, cognitive, and behavioural mechanisms for coping with the risk, all of which should be recognized in promoting physical activity among high‐risk individuals. <boxed-text content-type="box" id="bjhp12090-blkfxd-0001" position="anchor" orientation="portrait"> Statement of contribution What is already known on this subject? Diabetes screening has few adverse psychological effects on screened individuals. Diabetes can be prevented by increased physical activity and modest weight loss among high‐risk individuals. The evidence on the effects of screening on protective behaviour is limited and inconsistent. What does this study add? High‐risk individuals' threatening perception of risk appears encouraging increased physical activity. Individuals having problems in adjusting to high‐risk identification may not be motivated to engage in physical activity for prevention. Failure to achieve the outcomes expected from lifestyle changes may lead people with threatening risk perception to a sense of hopelessness. </boxed-text>